Pentraxin 3 Levels in Young Women with and without Polycystic Ovary Syndrome (PCOS) in relation to the Nutritional Status and Systemic Inflammation - Wyskida, Katarzyna (Int J Endocrinol, 2020)
OBJECTIVE: The aim of the study was to assess PTX3 levels in PCOS and non-PCOS women in relation to nutritional status and circulating markers of inflammation. METHODS: The study enrolled 99 stable body mass PCOS women (17 normal weight, 21 overweight, and 61 obese) and 61 non-PCOS women (24 normal weight, 19 overweight, and 18 obese). Body composition was assessed by bioimpedance, and plasma levels of pentraxin 3 (PTX3), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and monocyte chemoattractant protein 1 (MCP-1) were measured. Homeostatic model assessment of insulin resistance (HOMA-IR) was made. RESULTS: Plasma PTX3, TNF-α, and IL-6 levels and HOMA-IR were higher in PCOS than in non-PCOS group (p < 0.001). There were positive correlations between log(10) (PTX3) and log(10) (BMI), waist circumference and fat percentage, as well as log(10) (HOMA-IR) and free androgen index but negative between log(10) (estradiol) levels in PCOS. While in the non-PCOS group, the correlations between log(10) (PTX3) and log(10) (BMI), waist circumference and fat percentage, as well as log(10) (HOMA-IR) were negative. The positive correlations between PTX3 and MPC-1 and log(10) (IL-6) were shown in the PCOS group only. In multivariate regression analyses, variability in PTX3 levels in the PCOS group was proportional to log(10) (BMI), waist circumference, and fat percentage, but inversely proportional to log(10) (estradiol) levels. While in the non-PCOS group, PTX3 levels were inversely proportional to all anthropometric parameters. CONCLUSIONS: Our results show that the decrease in PTX3 levels observed in obese is distorted in PCOS by microinflammation, and possibly, dysfunction of stroma adipose tissue and liver steatosis is reflected by enhanced insulin resistance.